2009
DOI: 10.1002/bdrb.20193
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development in cynomolgus monkeys following prenatal exposure to natalizumab, an α4 integrin inhibitor

Abstract: Natalizumab had no adverse effects on the general health, survival, development, or immunological structure and function of infants born to dams treated with natalizumab during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 25 publications
1
46
0
1
Order By: Relevance
“…Based on animal studies of embryonic and post-natal development it has been deemed that prolonged, high dose natalizumab treatment caused no developmental defects 85-87. These results cannot be extrapolated to other α4 antagnoists.…”
Section: α4 Integrinsmentioning
confidence: 99%
“…Based on animal studies of embryonic and post-natal development it has been deemed that prolonged, high dose natalizumab treatment caused no developmental defects 85-87. These results cannot be extrapolated to other α4 antagnoists.…”
Section: α4 Integrinsmentioning
confidence: 99%
“…Studies of natalizumab in MS have shown reduced relapse rates and disability progression, but less is known about its effects on pregnancy outcomes [10, 11]. Natalizumab is classified as a pregnancy category C drug, as potential fetal effects have been reported in animal studies [1214] and there is a paucity of well-controlled human studies [6]. Although some animal studies have shown that natalizumab can cross the placental barrier and produce hematologic effects on fetal guinea pigs and primates [6, 12, 14, 15], others have not shown fetal interaction [16].…”
Section: Introductionmentioning
confidence: 99%
“…Natalizumab is classified as a pregnancy category C drug, as potential fetal effects have been reported in animal studies [1214] and there is a paucity of well-controlled human studies [6]. Although some animal studies have shown that natalizumab can cross the placental barrier and produce hematologic effects on fetal guinea pigs and primates [6, 12, 14, 15], others have not shown fetal interaction [16]. Human studies and case reports have not shown increases in spontaneous abortions or birth defects; however, results are limited by small sample sizes [17–20].…”
Section: Introductionmentioning
confidence: 99%
“…Few dams had measurable natalizumab in the breast milk, and IgG antibodies are not subject to significant transport out of the gut and into the circulation of primates. 6 …”
mentioning
confidence: 99%